2021
DOI: 10.3390/ijms22020604
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the Citric Acid Cycle: Connecting Pyruvate Carboxylase and Citrate Synthase to the Flow of Energy and Material

Abstract: In 1937, Sir H. A Krebs first published the Citric Acid Cycle, a unidirectional cycle with carboxylic acids. The original concept of the Citric Acid Cycle from Krebs’ 1953 Nobel Prize lecture illustrates the unidirectional degradation of lactic acid to water, carbon dioxide and hydrogen. Here, we add the heart lactate dehydrogenase•proton-linked monocarboxylate transporter 1 complex, connecting the original Citric Acid Cycle to the flow of energy and material. The heart lactate dehydrogenase•proton-linked mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…By proteomics, we detected significant increases in electron transport chain (ETC) factors, COX7A2 and UQCRSF , and a decrease in ETC components, COX6A1 and NDUFB7 ( Figure 3 C) [ 57 ]. While not statistically significant, there were also trends toward increased citric acid cycle-related enzymes, IDH1 , IDH2 , and PDHB ( Figure 3 C) [ 58 ]. A significant increase in L2HGDH may also increase the levels of α-ketoglutarate, a metabolite also produced by isocitrate dehydrogenase ( Figure 3 D) [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…By proteomics, we detected significant increases in electron transport chain (ETC) factors, COX7A2 and UQCRSF , and a decrease in ETC components, COX6A1 and NDUFB7 ( Figure 3 C) [ 57 ]. While not statistically significant, there were also trends toward increased citric acid cycle-related enzymes, IDH1 , IDH2 , and PDHB ( Figure 3 C) [ 58 ]. A significant increase in L2HGDH may also increase the levels of α-ketoglutarate, a metabolite also produced by isocitrate dehydrogenase ( Figure 3 D) [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…GAPDH catalyzes the sixth step of glycolysis, converting glyceraldehyde 3-phosphate to D-glycolic acid 1, 3-diphosphate ( Colell et al, 2009 ). CS catalyzes the condensation of oxaloacetic acid and acetyl-coA to produce citric acid, which is the key regulating step of the tricarboxylic acid (TCA) cycle ( Roosterman and Cottrell, 2021 ). The downregulated expression of GAPDH and CS genes in this study indicated that 96 h of air exposure suppressed the glycolysis and TCA cycle of C. fluminea.…”
Section: Discussionmentioning
confidence: 99%
“…NADH H + and FADH 2 are key shuttles for the passage of high-energy electrons to the terminal electron acceptor O 2 via an array of electron carriers known as the electron transport chain (ETC). The ETC's major function is to create an electrochemical gradient across the mitochondrial inner membrane (IMM), which is essential for chemiosmotic ATP synthesis (OXPHOS) [29]. Importantly, the TCA cycle serves as a source of precursors for many other biological compounds, including non-essential amino acids, nucleotide bases, and porphyrin [27].…”
Section: Tricarboxylic Acid Cyclementioning
confidence: 99%